1998
DOI: 10.1161/01.cir.97.5.473
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Myocardial Blood Flow With Ultrasound-Induced Destruction of Microbubbles Administered as a Constant Venous Infusion

Abstract: Background-Ultrasound can cause microbubble destruction. If microbubbles are administered as a continuous infusion, then their destruction within the myocardium and measurement of their myocardial reappearance rate at steady state will provide a measure of mean myocardial microbubble velocity. Conversely, measurement of their myocardial concentration at steady state will provide an assessment of microvascular cross-sectional area. Myocardial blood flow (MBF) can then be calculated from the product of the two. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
1,225
3
19

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 1,526 publications
(1,275 citation statements)
references
References 26 publications
20
1,225
3
19
Order By: Relevance
“…Wei et al (31) and Foltz et al (24) observed a mismatch between increased perfusion and a nearly constant blood volume with intracoronary infusion of adenosine in dogs and pigs. In contrast, with the same type of infusion in pigs, Mohlenkamp et al (32) detected a proportional increase in both MBF and MBV using an electron-beam computed tomography technique.…”
Section: Discussionmentioning
confidence: 98%
“…Wei et al (31) and Foltz et al (24) observed a mismatch between increased perfusion and a nearly constant blood volume with intracoronary infusion of adenosine in dogs and pigs. In contrast, with the same type of infusion in pigs, Mohlenkamp et al (32) detected a proportional increase in both MBF and MBV using an electron-beam computed tomography technique.…”
Section: Discussionmentioning
confidence: 98%
“…It is the detection of these non-linear components which is at the basis of contrast-specific modalities such as contrast harmonic (Burns et al 1996) and pulse inversion imaging and contrast Doppler (Hope Simpson et al 1999), which are used to suppress tissue signals and enhance blood echo, particularly at the level of the smaller blood vessels. As the pressure amplitude is further increased, contrast agent disruption takes place with the emission of a strong and brief nonlinear echo, which is relatively easy to detect and allows the evaluation of tissue perfusion because of the modification of the signal intensity of the image (Wei et al 1998). New emerging areas of ultrasound-contrast imaging research are in the targeting of the bubbles to specific sites, such as blood clots (Takeuchi et al 1999) or endothelial cells (Lindner et al, 2000) and the imaging of angiogenic vessels by high frequency ultrasound exposure (Foster et al 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, recent studies have shown that microbubbles can be destroyed by ultrasound and that measurements of their kinetics can be used to quantify tissue perfusion (21,22). During a continuous infusion of microbubbles at steady state, measurement of the rate at which microbubbles replenish tissue after their ultrasound-induced destruction could provide an evaluation of blood flow in the canine kidney (21) and in the heart (22). To our knowledge, however, such a technique has not been applied to evaluation of the human kidney.…”
Section: Introductionmentioning
confidence: 99%